Studi Tata Kelola Perusahaan yang Baik melalui Kinerja Perusahaan: Studi Pemetaan Sistematik - Nurjamilah Nurjamilah; Muhamad Rizal; Ria Arifianti (Universitas Winaya Mukti, 2018)
The implementation of Good Corporate Governance is a concept that emphasizes the importance of the rights of shareholders to obtain information correctly, accurately, and on time. But a thorough understanding of the state-of-art of Good Corporate Governance is needed. Therefore, this article aims to classify, identify scientific publications and conduct thematic analyzes of the current literature to create extensive and detailed understanding in the field of Good Corporate Governance. The research method is carried out by means of the Systematic Mapping Study (SMS) to study scientific publications in the field of Good Corporate Governance which are based on the focus and type of research from time to time. The results of this study resulted in the categorization and quantification of the Good Corporate Governance study in various dimensions as well as an overview of current research topics and trends.